Strange situation : a mother's journey into the science of attachment - Saltman, Bethany (Ballantine Books, 2020)
"When professional researcher and writer Bethany Saltman gave birth to her daughter, Azalea, she loved her deeply but felt as if something was missing. Looking back at her lonely childhood, dangerous teenage years, and love-addicted early adulthood, Saltman thought maybe she was broken. Then she discovered the science of attachment, the field of psychology that explores the question of why- from an evolutionary point of view- love exists between parents and children. Saltman went on a ten-year journey visiting labs, archives, and training sessions, while learning the meaning of delight from Mary Ainsworth, one of psychology's most important but unsung researchers, who died in 1999. Saltman went deep into the history and findings from Ainsworth's famous laboratory procedure, the Strange Situation, which, like an X-ray, is still used today by scientists around the world to catch a glimpse of the internal workings of attachment. In this simple twenty-minute procedure, a baby and a caregiver enter an ordinary room with two chairs and some toys. During a series of comings and goings, a trained observer studies the minutiae of the pair's back-and-forth with each other. Through the science of attachment, what Saltman discovered was a radical departure from everything she thought she knew- about love and about her own family, her story, and herself. She was far from broken- she saw that love is too powerful to ever break. Strange Situation is a scientific, lyrical, life-affirming exploration of love. Not only will readers be taken on an emotional ride through one mother's reckoning with her own past and her family's future, but they will also be given the tools with which to better understand their own life histories and their relationships today." Jacket flap.